Potential Human Health Risk from Toxic/Carcinogenic Arsenic in Ripe and Unripe Tomatoes Grown in Wastewater Exposed Zone - Topal, Murat; Topal, E.ışıl Arslan; Öbek, Erdal (My University, 2024)
The aim of the present study was to investigate the potential risk to human health from toxic/carcinogenic arsenic in ripe (RiTo) and unripe tomatoes (UnRiTo) grown in the municipal wastewater treatment plant effluents exposure zone. The arsenic concen-trations were determined in each tissue of RiTo and UnRiTo tomatoes. Arsenic values in tomatoes were root>leaf>unripe tomato>ripe tomato>stem. The maximum ED (exposure dose) value in RiTos was 1.21E-02 mg.kg-1.day-1 for child, minimum ED value was 4.80E-03 mg.kg-1.day-1 for male. The ED value was calculated as 5.44E-03 mg.kg-1.day-1 for female. The maximum ED value in UnRiTo was 2.12E-02 mg.kg-1.day-1 for child, min ED value was 8.39-03 mg.kg-1.day-1 for male. ED value was calculated as 9.51E-03 mg.kg-1.day-1 for female. EDs in RiTo and UnRiTo were child>female>male. When the HQs (hazard quotient) in RiTo and UnRiTo compared, HQ values in UnRiTo were higher. All of the HQ values were higher than 1. As a re-sult, results of tomatoes analysis show that there was non-carcinogenic and carcino-genic health risks.
Keywords: Wastewater; health risk; Arsenic; tomatoes; carcinogenic